The Green Revolution shaped the population structure of the rice pathogen Xanthomonas oryzae pv. oryzae - Quibod, Ian Lorenzo; Atieza-Grande, Genelou; Oreiro, Eula Gems; Palmos, Denice; Nguyen, Marian Hanna; Coronejo, Sapphire Thea; Aung, Ei Ei; Nugroho, Cipto; Roman-Reyna, Veronica; Burgos, Maria Ruby; Capistrano, Pauline; Dossa, Sylvestre G.; et al. (Oxford University Press, 2020)
The impact of modern agriculture on the evolutionary trajectory of plant pathogens is a central question for crop sustainability. The Green Revolution replaced traditional rice landraces with high-yielding varieties, creating a uniform selection pressure that allows measuring the effect of such intervention. In this study, we analyzed a unique historical pathogen record to assess the impact of a major resistance gene, Xa4, in the population structure of Xanthomonas oryzae pv. oryzae (Xoo) collected in the Philippines in a span of 40 years. After the deployment of Xa4 in the early 1960s, the emergence of virulent pathogen groups was associated with the increasing adoption of rice varieties carrying Xa4, which reached 80% of the total planted area. Whole genomes analysis of a representative sample suggested six major pathogen groups with distinctive signatures of selection in genes related to secretion system, cell-wall degradation, lipopolysaccharide production, and detoxification of host defense components. Association genetics also suggested that each population might evolve different mechanisms to adapt to Xa4. Interestingly, we found evidence of strong selective sweep affecting several populations in the mid-1980s, suggesting a major bottleneck that coincides with the peak of Xa4 deployment in the archipelago. Our study highlights how modern agricultural practices facilitate the adaptation of pathogens to overcome the effects of standard crop improvement efforts.